High pressure processing inactivates human cytomegalovirus and hepatitis A virus while preserving macronutrients and native lactoferrin in human milk. (January 2022) - Pitino, Michael A.; Unger, Sharon; Gill, Alexander; McGeer, Allison J.; Doyen, Alain; Pouliot, Yves; Bazinet, Richard P.; Kothari, Akash; Mazzulli, Tony; Stone, Debbie; O'Connor, Deborah L.
Abstract: The effect of high pressure processing (HPP) compared to Holder pasteurization (HoP) (62.5 °C, 30 min), on the inactivation of cytomegalovirus (CMV) and hepatitis A virus (HAV) inoculated human milk pools ( n  = 10) and culture media ( n  = 3) was studied. Samples were retained as untreated controls, treated by HoP (62.5 °C, 30 min) or with one of six different HPP protocols (350 MPa, 500 MPa, 600 MPa for 8- or 10-min at <10 °C). Macronutrient concentration and lactoferrin were measured to confirm milk quality. Both HPP and HoP reduced CMV by >4.8-log PFU/mL and >0.9-log PFU/mL in culture medium and human milk, respectively. HoP reduced HAV by 3.4-log PFU/mL and 3.1-log PFU/mL in culture medium and human milk, respectively. HPP treatments of 500 or 600 MPa reduced HAV by >5.7-log PFU/mL and >4-log PFU/mL in culture medium and in human milk, respectively. Macronutrients (fat, total protein, carbohydrate) and energy composition was not affected by any treatment. Lactoferrin concentration decreased by 35% ± 21% (SD) after HoP, but not HPP. Industrial relevance: This study confirms that HPP is effective in inactivating representative enveloped and non-enveloped viruses in human milk and reducing bacterial load, with no adverse effect on macronutrient and energy composition. For these reasons, evidence it reduces bacteria, and increased efficiency in which milk can be processed, HPP shows great promise in replacing HoP in human milk banking. Highlights: Exposure to 500 MPa 8 min reduced cytomegalovirus (>0.9-log) similar to Holder pasteurization. Exposure to 500 MPa 8 min reduced hepatitis A virus (>4-log) compared to Holder pasteurization (3.1-log). High pressure processing and Holder pasteurization reduced bacterial load to below 1 CFU/mL. Pressure did not alter the nutritional composition of milk, including lactoferrin.